Family roles and limitations as mediators in medical communication for cancer patients: A qualitative study - Yeori Park; Jiyeon Kang; Yeonju Kim; Young Su Park; Sang-Ho Yoo (PLoS ONE, 2025)
This qualitative study explored the role and limitations of families as mediators of medical communication among cancer patients in South Korea. Semi-structured interviews were conducted with 46 participants including patients, family members, doctors, and nurses. This study examined how families alleviate communication burdens and navigate power dynamics between patients and physicians. The findings revealed that families gather, interpret, and translate medical information, often acting as intermediaries, owing to limited consultation times and complex medical terminology. They provide emotional, financial, and integrated care; influence treatment decisions; and ensure compliance. However, the study also identified limitations, such as disagreements among family members, information concealment, and the potential undermining of patient autonomy. This study underscores the need for nuanced approaches to family involvement that prioritize patient-centered care and respect individual preferences.